2019
DOI: 10.1016/j.actamat.2019.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Monoclinic angle, shear response, and minimum energy pathways of NiTiCu martensite phases from ab initio calculations

Abstract: Ti50Ni50-xCux alloys are observed to exhibit multiple martensitic transformations from B2 to an orthorhombic B19 and a monoclinic B19′ phase. In addition, DFT calculations have predicted a B19ʺ phase with a higher monoclinic angle as the thermodynamically stable ground state. This study investigated the effects of Cu content and shear stress on the monoclinic angles, phase stabilities of the various martensites, the minimum energy pathways, and the relative total energies among the phases in this pseudo-equiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…In these analyses B19″ was absent (not mentioned). In our recent work using ab initio calculation to analyse the phase stabilities in NiTi [24], we found that the B19′ phase is in fact a mechanically distorted state of B19″ instead of a phase in its own right with a local energy minimum. In this regard, the effect of an opposing shear stress may be described as to destabilise the BCO phase relative to B19″ and at the same time to reduce the monoclinic angle of B19″ to that of the observed B19′ phase.…”
Section: Introductionmentioning
confidence: 97%
“…In these analyses B19″ was absent (not mentioned). In our recent work using ab initio calculation to analyse the phase stabilities in NiTi [24], we found that the B19′ phase is in fact a mechanically distorted state of B19″ instead of a phase in its own right with a local energy minimum. In this regard, the effect of an opposing shear stress may be described as to destabilise the BCO phase relative to B19″ and at the same time to reduce the monoclinic angle of B19″ to that of the observed B19′ phase.…”
Section: Introductionmentioning
confidence: 97%
“…In recent scientific literature, interest was devoted to nano-structuration by ball milling and to preparation by sintering processes from powders [ 19 , 20 , 21 , 22 ]. Moreover, several studies involve theoretical calculations and simulations to correlate the macroscopic and functional properties of NiTi alloys to microstructural characteristics and to explore the martensitic path and evolution [ 23 , 24 , 25 , 26 ]. Concerning the damping properties, the grain size, martensite interface density, and defect structure are important internal variables and, in the case of NiTiCu, the Cu addition enhances the behavior of the NiTi system [ 5 , 27 ].…”
Section: Introductionmentioning
confidence: 99%